Endoscopic argon plasma coagulation treatment for late dumping syndrome in patients with Roux-en-Y gastric bypass - Mera-Carreiro, Sara; Bernaldo-Madrid, Blanca; Rodríguez-Carrillo, Clara; Esteban-López-Jamar, José Miguel; Marcuello-Foncillas, Clara; Pérez-Ferre, Natalia; Ramos-Leví, Ana; Matía-Martín, Pilar; Rubio-Herrera, Miguel Ángel (Frontiers in Endocrinology, 2025)
IntroductionDumping syndrome (DS) and postprandial hypoglycemia (PPH) are challenging complications encountered after Roux-en-Y gastric bypass (RYGB). Surgical revision is often the next therapeutic step when pharmacological and dietary treatments fail to control DS and PPH. Endoscopic argon plasma coagulation (APC) is a less invasive alternative that reduces the diameter of the gastrojejunal anastomosis (GJA). The aim of the study is to evaluate the efficacy and safety of APC in managing postprandial hypoglycemia (PPH) after RYGB.MethodsThis retrospective study included patients who underwent endoscopic APC for GJA reduction between 2018 and 2022. Improvement of PPH, and anthropometric data were evaluated.ResultsTwenty-five patients aged 52.3 ± 9.2 years, with PPH and poor response to pharmacological treatment, were recruited. All patients had an average of two APC endoscopic procedures (range 1–4), initial GJA diameter of 26.8 ± 7.2 mm, and post-APC diameter of 16.4 ± 4.4 mm. Adverse events were mild and did not require hospitalization. Symptoms improved in 100% of patients with a decrease in Sigstad score from 8.2 ± 1.9 to 0.9 ± 2 (p < 0.0001) and resolution of PPH (p < 0.0001) over the 24-month follow-up. Of these, 84% discontinued pharmacological treatment. In addition, 60% of the patients who regained weight from the nadir after RYGB had a significant percentage of total body weight loss (% TBW) (p < 0.01) after APC during the 2-year follow-up.ConclusionAPC is effective, safe, and reproducible in managing PPH in patients who undergo RYGB, refractory to dietary and pharmacological treatments. It also contributes to weight loss after weight regain.